The Influence Of Price And Product Quality On The Business Success Of Coffee Traders In Kepahiang Regency - Sidik Maulana; Nirta Vera Yustanti; Kimas Kurniawan Tando Agung (Utami Publisher, 2026)
This study aims to analyze the effect of price and product quality on the business success of coffee traders (Toke Kopi) in Kepahiang Regency, both partially and simultaneously. This study uses a quantitative method with an associative-causal approach. The study population consisted of 75 active coffee traders, and a sample of 43 respondents was taken using a saturated sampling technique. Data were collected through questionnaires and then analyzed using multiple linear regression with the assistance of SPSS version 27. The results show that partially, price and product quality have a positive but not significant effect on business success. Simultaneously, the two variables also do not have a significant effect, with a significance value of 0.067 > 0.05 and a coefficient of determination (R²) of 12.6%. This indicates that 87.4% of other variables outside the study also influence business success, such as capital, marketing networks, and relationships with farmers. This study concludes that price and product quality are not yet the primary factors determining the business success of coffee traders in Kepahiang Regency.